Integration of Ukraine into the European banking system: cleaning, rebooting and Basel III - Ramskyi, Andriy; Loiko, Valeria; Sobolieva-Tereshenko, Olena; Loiko, Daria; Zharnikova, Valeriia; Лойко, Дарія (LLC CPC Business Perspectives, 2017)
The urgency of the issue is related to changes in the Ukrainian banks' business environment, taking into account the impact of domestic and global financial instability and the implementation of the regulatory framework for banking regulation of the National Bank of Ukraine in accordance with the Basel Committee on Banking Supervision recommendations. The main goal of this research is to analyze the degree of implementation and compliance with the Basel III regulations in Ukrainian banking system. To carry out the research, regulatory and legislative documents of the National Bank of Ukraine, the Basel Accords, statistic data of the Ukrainian banks and the National Bank of Ukraine were used. For this purpose, the analysis of main indicators of Ukrainian banks' financial stability within the period of 2014-2017 is made. Thus, post-crisis regulatory changes have aimed at restoring bank stability. The results seem to suggest that bank regulatory changes may be repressive, for instance, cleaning and optimization of the banking system as an effective tool for anticrisis management. As a result, it was concluded that banks with foreign capital are the most stable in the banking system of Ukraine in comparison with domestic banks. © 2017 Andriy Ramskyi.
Keywords: Bank efficiency; Banking regulation; Banking system; Banks; Banks' activities; Basel; Crisis; National Bank of Ukraine; Risk management